1998
DOI: 10.1055/s-2006-957489
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoid Composition of the Wound-Induced Bark Exudate ofCommiphora tenuisfrom Ethiopia

Abstract: The bark of Commiphora tenuis Vollensen exudes a translucent, free-flowing odoriferous liquid upon wounding which was analysed by capillary GLC and GLC-MS. 42 mono- and sesquiterpenes were detected and 37 identified. The main components of the monoterpenoid fraction were alpha-pinene (60.8%), beta-pinene (8.8%), sabinene (6.3%), alpha-thujene (8.9%), limonene (5.5%), 3-carene (3.7%), beta-myrcene (1.8%), and beta-elemene (1.1%) constituting 97% of the oil. Identified sesquiterpenoid components constituted appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Generally, among the investigated extracts the methanolic extracts exhibited the highest antibacterial effect followed by the chloroform extracts. The most pronounced activity with inhibition zones of more than 14 mm was shown by the methanolic extracts of Boswellia Although other species of the genera Boswellia (Adelakun et al, 2001), Buxus (Rahman et al, 1997), Commiphora (Asres et al, 1998), Jatropha (Aiyelaagbe et al, 2000), Punica (Machado et al, 2002), Withania (Budhiraja et al, 2000), Kalanchoe (Asiedu-Gyekye et al, 2002), Cissus (Beltrame et al, 2002) and Cleome (Samy et al, 1999) have been subjected to several studies and antimicrobial activities have been found, nothing is known about the species reported here. The results obtained in the course of the present study are in agreement to a certain degree with the traditional uses of the plants evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, among the investigated extracts the methanolic extracts exhibited the highest antibacterial effect followed by the chloroform extracts. The most pronounced activity with inhibition zones of more than 14 mm was shown by the methanolic extracts of Boswellia Although other species of the genera Boswellia (Adelakun et al, 2001), Buxus (Rahman et al, 1997), Commiphora (Asres et al, 1998), Jatropha (Aiyelaagbe et al, 2000), Punica (Machado et al, 2002), Withania (Budhiraja et al, 2000), Kalanchoe (Asiedu-Gyekye et al, 2002), Cissus (Beltrame et al, 2002) and Cleome (Samy et al, 1999) have been subjected to several studies and antimicrobial activities have been found, nothing is known about the species reported here. The results obtained in the course of the present study are in agreement to a certain degree with the traditional uses of the plants evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of furanosesquiterpenoids is characteristics of this genus. Asres et al (1998) More than twenty furanosesquiterpenoids covering furanogermacrane, furanoeudesmanes, furanoguaiane, furanocadinane and furanoelemane have been discovered (Table S1 and Fig. S1), since the first isolation of furanosesquiterpenoid from C. molmol (Brieskorn and Noble, 1980).…”
Section: Monoterpenoids Sesquiterpenoids and Volatile Oilmentioning
confidence: 99%
“…The column (DB-1) temperature program adopted for the n-hexane-ether extract was raised at a rate of 6 ∞C/ min from 70Ð300 ∞C, other conditions were identical to those mentioned above. Identification of the constituents was performed by computer liberary search, retention indices and visual interpretation of mass spectra with those found in the literature (El-Shazly, 1999;Adams, 1995;Asres et al, 1998, Masada, 1967Ryhage and Sydow, 1963;Sydow, 1963). The identified compounds are recorded in Table I.…”
Section: Glc-msmentioning
confidence: 99%